Gambling expenditure predicts harm: evidence from a venue‐level study. (5th June 2014) - Markham, Francis; Young, Martin; Doran, Bruce
Abstract Background and Aims The Total Consumption Theory of gambling suggests that gambling expenditure is positively associated with gambling‐related harm. We test the hypothesis that electronic gaming machine (EGM) expenditure predicts gambling‐related harm at the level of the EGM venue. Design Cross‐sectional analysis of survey and administrative data. Setting General urban adult population of the Northern Territory of Australia. Participants The sample consisted of 7049 respondents to a mail‐survey about venue visitation and gambling behaviour across 62 EGM venues. Measurements Gambling‐related harm was defined as the endorsement of two or more items on the Problem Gambling Severity Index. We obtained venue‐level EGM expenditure data from the local licensing authority for all venues in the study area. We compared the prevalence of gambling‐related harm among patrons aggregated at the venue level with the estimated mean EGM expenditure for each adult resident in the venue's service area using a Huff model, correlation analysis and multivariate binomial regression. Findings Aggregated to the venue level (n = 62), per‐capita EGM expenditure was correlated significantly with rates of gambling‐related harm (r = 0.27, n = 62, P = 0.03). After adjusting for venue type and number of EGMs, an increase in mean per‐capita monthly EGM expenditure from AU10 to AU150 was associated with a doubling in the prevalence of gambling‐related harm from 9% (95% CI = 6–12%) to 18% (95% CI = 13–23%). Conclusions As suggested by the Total Consumption Theory of gambling, aggregate patron electronic gaming machine expenditure predicts the prevalence of gambling‐related harm at the venue level.